Effect of T.S.S. and pH Levels on Quality of Kokum (Garcinia indica) Wine - SARKALE, A. N.; PAWAR, C. D. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Wine was prepared from the kokum fruits with different T.S.S. and pH levels of must to study their effect on quality of kokum wine. Five levels of T. S. S. viz, 20, 25, 30, 35, 40 0Brix and three pH levels viz, 3.0, 3.5, 4.0 were selected to prepare fifteen types of kokum wine samples. T. S. S., reducing sugars and pH of the wine was increased with increase in T.S.S. levels of fruit. No specific trend of anthocyanin and tannin content was observed with increase in T.S.S. levels. The wine prepared from 25 0Brix T. S. S. level and 4.0 pH was found to be best considering the